2009
DOI: 10.1038/sj.bdj.2009.804
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of symptoms in previously symptom-free impacted lower third molars assessed in general dental practice

Abstract: million per annum 1 and around £22 million to the private sector. 2 The enormous number of teeth removed in the UK prompted researchers to assess the type of practice conducted here and in 1998 a study had estimated that around 20-30% of third molars that were removed in the UK did not fulfi l the American National Institutes of Health criteria for removal and were, therefore, removed prophylactically. 3 This was followed by the publication of guidelines by the NICE 4 and SIGN 5 on the management of impacted l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 15 publications
4
20
0
2
Order By: Relevance
“…The mean age of patients with impactions as was found in this study was slightly higher compared to reports from Europe and America [3,20]. This might be explained by the fact that in those countries impactions are discovered during routine dental examinations which start at younger ages [28-30]. On the other hand in resource poor countries and for Tanzania in particular, majority of the patients report for health care only after experiencing symptoms that lead to a certain degree of incapacitation which varies from mild to severe pain, swellings, trismus or fever.…”
Section: Discussionmentioning
confidence: 62%
“…The mean age of patients with impactions as was found in this study was slightly higher compared to reports from Europe and America [3,20]. This might be explained by the fact that in those countries impactions are discovered during routine dental examinations which start at younger ages [28-30]. On the other hand in resource poor countries and for Tanzania in particular, majority of the patients report for health care only after experiencing symptoms that lead to a certain degree of incapacitation which varies from mild to severe pain, swellings, trismus or fever.…”
Section: Discussionmentioning
confidence: 62%
“…The literature shows that tooth impaction is a frequent phenomenon; 3–14 however, there is considerable variation in the prevalence and distribution of impacted teeth in different regions of the jaw 4–14 . Factors affecting the prevalence include the selected age group, timing of dental eruption, and the radiographic criteria for dental development and eruption.…”
Section: Introductionmentioning
confidence: 99%
“…Tooth-related pain is strongly correlated with untreated dental disease (dental decay); in addition, fractured teeth and exposed dentin due to attrition, erosion, and abrasion may also cause pain. Impacted third molars also cause pain; 23 % of partially erupted impacted third molars develop pain symptoms compared to 10 % of unerupted [ 12 ]. It is also reported that tooth-related disease and pain in children are inversely associated with educational levels of parents [ 13 , 14 ] as well as educational levels of individuals [ 15 , 16 ].…”
Section: Tooth-related Orofacial Painmentioning
confidence: 95%